2019
DOI: 10.3389/fnins.2019.00680
|View full text |Cite
|
Sign up to set email alerts
|

From Cannabinoids and Neurosteroids to Statins and the Ketogenic Diet: New Therapeutic Avenues in Rett Syndrome?

Abstract: Rett syndrome (RTT) is an X-linked neurodevelopmental disorder caused mainly by mutations in the MECP2 gene, being one of the leading causes of mental disability in females. Mutations in the MECP2 gene are responsible for 95% of the diagnosed RTT cases and the mechanisms through which these mutations relate with symptomatology are still elusive. Children with RTT present a period of apparent normal development followed by a rapid regression in speech and behavior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 262 publications
(409 reference statements)
0
13
0
1
Order By: Relevance
“…Another emerging option is natural constituents of the cannabis plant (CBD, reduces neuronal hyperexcitability through a unique multimodal mechanism of action), currently in the phase 3 clinical trial to test its efficacy for patients with RTT Epidiolex (NCT03848832). A ketogenic diet (high-fat, adequate-protein, low-carbohydrate diet, possibly acts through increased conversion of glutamate into GABA and activation of adenosine A1 receptors, which affects potassium channels and leads to membrane hyperpolarization), although rarely used in patients with RTT, seems to have a good effect according to rare available studies [ 223 , 224 , 225 ]. Thus, epilepsy is controlled in RTT mainly through blocking the action potentials by affecting sodium channels and through increase of GABA concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another emerging option is natural constituents of the cannabis plant (CBD, reduces neuronal hyperexcitability through a unique multimodal mechanism of action), currently in the phase 3 clinical trial to test its efficacy for patients with RTT Epidiolex (NCT03848832). A ketogenic diet (high-fat, adequate-protein, low-carbohydrate diet, possibly acts through increased conversion of glutamate into GABA and activation of adenosine A1 receptors, which affects potassium channels and leads to membrane hyperpolarization), although rarely used in patients with RTT, seems to have a good effect according to rare available studies [ 223 , 224 , 225 ]. Thus, epilepsy is controlled in RTT mainly through blocking the action potentials by affecting sodium channels and through increase of GABA concentration.…”
Section: Resultsmentioning
confidence: 99%
“…An additional 7 studies were added that did not come up on the search but were identified in reading the identified literature. Abstract-based screening identified 105 studies reporting EEG characteristics/epilepsy in RTT, including 21 reviews: one review was related to systematic review of event-related potentials in Rett syndrome [ 40 ] that is out of scope of the current review; and most others ( n = 11) focused on epileptiform discharges and seizures in patients with RTT [ 41 , 46 , 54 , 58 , 223 , 241 , 242 , 243 , 244 , 245 , 246 ]. One review was devoted to findings in RTT animal models [ 205 ].…”
Section: Methodsmentioning
confidence: 99%
“…CBDV has been investigated as a treatment for symptoms associated with autism spectrum disorder (ASD) such as repetitive behaviors, cognitive challenges and issues with communication and social functioning ( Mouro, et al, 2019 ). Mice carrying mutations in the MeCP2 gene and MeCP2 null mice develop Rett Syndrome (RTT), a neurodevelopment disease related to ASD.…”
Section: Minor Cannabinoid Pharmacology and Therapeuticsmentioning
confidence: 99%
“…Indeed, three clinical reports have recently established that CBD alleviates major symptoms associated with ASD, including seizures, sleeplessness, and anxiety, in children (Barchel et al, 2018; Aran et al, 2019; Bar-Lev Schleider et al, 2019). In addition, because CBD possess a weak affinity for CB 1 and CB 2 , it has no psychoactive effects and may even prevent some of the harmful consequences of THC (Zuardi et al, 2012; Morales et al, 2017; Mouro et al, 2019). Lastly, a commercially available, oral CBD extract (Epidiolex) has recently gained FDA-approval for treatment of drug-resistant epilepsy (Sekar and Pack, 2019), which can be an additional burden faced by ASD patients (Sansa et al, 2011; Kokoszka et al, 2017; Long et al, 2019).…”
Section: Microglial-endocannabinoid Signaling and Asdmentioning
confidence: 99%